2022
DOI: 10.3390/catal12060601
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Perovskite Catalysts for Efficient Overall Water Splitting

Abstract: Hydrogen is considered a promising clean energy vector with the features of high energy capacity and zero-carbon emission. Water splitting is an environment-friendly and effective route for producing high-purity hydrogen, which contains two important half-cell reactions, namely, the anodic oxygen evolution reaction (OER) and the cathodic hydrogen evolution reaction (HER). At the heart of water splitting is high-performance electrocatalysts that efficiently improve the rate and selectivity of key chemical react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 144 publications
1
16
2
Order By: Relevance
“…The oxidation states of A-site metal cation are generally fixed, and it is hardly to change by the redox reaction in the electrocatalytic process. [36,43] According to the apparent oxidation states of the doped atoms, we categorized and compiled the impacts of A-site doping on the electrocatalytic activities in perovskite oxides, including isovalent metal doping and heterovalent metal doping.…”
Section: A-site Dopingmentioning
confidence: 99%
See 2 more Smart Citations
“…The oxidation states of A-site metal cation are generally fixed, and it is hardly to change by the redox reaction in the electrocatalytic process. [36,43] According to the apparent oxidation states of the doped atoms, we categorized and compiled the impacts of A-site doping on the electrocatalytic activities in perovskite oxides, including isovalent metal doping and heterovalent metal doping.…”
Section: A-site Dopingmentioning
confidence: 99%
“…Oxygen vacancies in perovskites are the most favorable Schottky defects due to low-formation energies and stable structure of perovskites. [36,53,78] They were shown to greatly increase the electrocatalytic activities of perovskites. Additionally, the reaction process may change due to the oxygen vacancies.…”
Section: O-site Vacanciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the effective strategies that have been used to boost the electrocatalytic activity of perovskite, cationic doping to achieve the improved oxygen vacancy is particularly attractive. The A and B sites of perovskite-type oxides can be replaced by heterogeneous atoms to regulate the electronic structure of bulk oxides . According to the principle of charge balance, the oxidation state of transition metal elements at the B site may change when small amounts of elements with different valence states are added at the A site.…”
Section: Introductionmentioning
confidence: 99%
“…Several reviews have been reported, discussing Z-schemes for overall water splitting and specifically proposing mechanisms, design strategies, and challenges. [1,3,7,13,[18][19][20][21][22][23][24] The focus of this review is the optimization strategies of powder suspension and particulate sheet Z-scheme photocatalytic systems for overall water splitting; in particular, different optimization strategies for a powder suspension Z-scheme with a redox shuttle and particulate sheet Z-scheme are emphasized.…”
Section: Introductionmentioning
confidence: 99%